Coenseignement orthopédagogue-enseignant : collaborer et coplanifier pour soutenir la différenciation pédagogique au primaire. - France Dubé; France Dufour; Émilie Cloutier; Marie-Jocya Paviel
This text presents some results of a study conducted in three Quebec primary schools which have experimented co-teaching to implement educational differentiation in classes bringing together students with diverse learning needs. The dyads of co-teachers have planned and animated teaching-learning situations with a view to supporting everyone's learning with an inclusive aim. They were able to readjust their teaching, paying attention to identifying the priority needs of students in a context where the role of the special education teacher is now perceived differently, focusing on the success of everyone, in the classroom.